Rethinking farmer knowledge from soil to plate through narrative inquiry - Eric Bendfeldt (Thomas A. Lyson Center for Civic Agriculture and Food Systems, 2021)
This paper illustrates how farmer knowledge is generatively constructed and framed within an agroecological context to address the complexities of our food system more fully. For some, farmer knowledge is a hidden asset below the surface that acts as a reserve for sustaining and fortifying food system possibilities. We interviewed 12 self-identified smallholder farmers in Virginia using narrative inquiry as a dynamic methodology to explore the rhizomatic quality and mycorrhizal nature of smallholder farmers’ knowledge and experiences of soil, conservation, and place. The narrative inquiry method offered a participatory research approach to analyze how farmers perform their work in ways that extend across and are entangled with other domains of the food system that reflect agroecological values. Five primary themes were identified from the narrative inquiry data analysis by drawing upon the whole measures of community food systems as a values-based framework. Our findings illustrate how farmer praxis is reflective of and influenced by the ecological and sociopolitical ethos of land, food, health, and liberation. For scholar-practitioners, this research emphasizes the current claim for reevaluating and reconceptualizing research and outreach responses to mounting food system crises. The construction and expansion of farmer knowledge are not linear but rhizomatic and mycorrhizal in quality; therefore, scholar-practitioner responses to understanding and engaging with farmer knowledge systems should be amenable to a diversity of culturally dynamic systems of knowing that embody socio-eco relations and networks. Like others, we argue that an overemphasis on essentialist “best practices” and technocratic problem-solving does not adequately help us see these generative possibilities from soil to plate. Thus, we recommend that food system practitioners and researchers emphasize engaged listening, storytelling, and generative—not extractive—approaches as an epistemological frame for expanding our understanding of agroecology and food systems change.